Realidade estendida: a influência da tecnologia na experiência de consumo em jogos eletrônicos - Costa, Laura Maria Aguiar (2024)
Understanding reality as a continuous element that enables different points of contact with the consumer, it is possible to verify its application in the most diverse industries. Having experienced latent growth in recent years due to its technological advancement, the electronic games industry has stood out for its increasingly incisive use of immersive technologies, such as augmented reality and virtual reality. In this sense, a holistic understanding of the components of consumer behavior that lead to the use of such technologies in games becomes fundamental to foster better strategies in the field. Therefore, the objective of this work is to understand the relevance of continuous reality in the consumer experience in electronic games. To this end, a meta-analysis was carried out proposing an initial model with the variables present in the literature and calculating their effects. That said, agreements are made on the Theory of Uses and Gratifications based on the model and its antecedents and consequences for the use of the media. In the subsequent stage, interviews were carried out with consumers of XR games to deepen the understanding of the specificities and refinement of the proposed model. In the third and final stage, it was possible to develop a measurement model for parallel reality in electronic games. The structural model test took place with a sample of 502 interviewees who identified themselves as users of games with immersive technologies. The answers were proven through structural equation modeling (PLS-SEM) and the results indicated that performance, social interaction and entertainment act as predecessors to usage behavior and challenge, achievement and recommendation act as consequences of the behavior . The purchasing behavior of in-game items or accessories is significantly demonstrated in the model.